Diaphragm and preparation method thereof, preparation process of battery, battery and electric device
By using a separator containing sodium supplementary compounds in sodium ion batteries, the problem of sodium ion loss during the first charging and discharging of sodium ion batteries is solved, and the improvement of battery circulation performance and the improvement of separator performance is achieved.
Patent Information
- Application Number
- CN202311032763.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-16
AI Technical Summary
During the first charging and discharging process, sodium ion batteries are irreversible due to the formation of solid electrolyte membranes, which leads to sodium ion loss in the positive electrode material and reduces the energy density.
A separator including a sodium supplement compound is used, and the chemical formula of the sodium supplement compound is NaAlO2 or Na2MnO2n+1, where M includes Ti, Zr, Si, 1≤n≤10. The sodium supplement compound decomposes during the process of decomposition or charging to produce sodium ions and inorganic materials, which improves the high-temperature shrinkage and puncture resistance of the membrane.
The sodium ions obtained by decomposition are supplemented into or consumed during the charging process, and the circulation performance of the battery is improved, and the performance of the separator is improved through inorganic materials to enhance the overall performance of the battery.
Smart Images

Figure CN119495905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a diaphragm and a preparation method thereof, a battery preparation process, a battery and an electrical device. Background Art
[0002] Compared with lithium-ion batteries due to the scarcity of elements such as lithium, cobalt and nickel, sodium-ion batteries have the advantages of abundant sodium resources and low raw material costs, which makes sodium-ion batteries have great development prospects in the field of energy storage.
[0003] Due to some irreversible reactions such as the formation of the solid electrolyte membrane (SEI membrane) on the negative electrode surface during the initial charge and discharge formation process, the positive electrode material will lose sodium ions, which will lead to a decrease in the energy density of sodium ion batteries. In view of this situation, it is urgent to develop some sodium supplementation materials and methods that meet the requirements. Summary of the invention
[0004] The main object of the present invention is to provide a separator aimed at improving the performance of sodium secondary batteries.
[0005] To achieve the above object, the present invention provides a diaphragm, the diaphragm includes a sodium supplement compound, the chemical formula of the sodium supplement compound is NaAlO2, Na2M n O 2n+1 At least one of, wherein M includes at least one of Ti, Zr, and Si, and 1≤n≤10.
[0006] The above-mentioned sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the formation or charging process. The product sodium ions can replenish the sodium ions consumed during the formation or charging process, and the product inorganic materials can improve the high-temperature shrinkage and puncture resistance of the diaphragm, thereby effectively improving the cycle performance of the battery.
[0007] Optionally, 1≤n≤5.
[0008] Sodium supplement compound Na2M n O 2n+1 In the range of 1≤n≤5, sodium supplement compounds with n in the above range are relatively common in nature, easy to obtain and relatively low in cost.
[0009] Optionally, the Na2M n O 2n+1 Including Na2TiO3, Na2Ti2O5, Na2Ti5O 11 、Na2Ti6O 13 , Na2ZrO3, Na2SiO3, Na2Si2O5, Na2Si3O7, Na2Si5O 11 、Na2Si 10 O 21At least one of .
[0010] Na2M in this application n O 2n+1 Including but not limited to Na2TiO3, Na2Ti6O 13 、Na2Ti5O 11 , Na2ZrO3, Na2SiO3, Na2Si2O5, Na2Si3O7, Na2Si5O 11 、Na2Si 10 O 21 It is understandable that the sodium supplement compound can be oxidized and decomposed during the formation or charging process to obtain sodium ions and inorganic materials.
[0011] For example, 4NaAlO2-4e-→2Al2O3+4Na + +O2;
[0012] Or, 2Na2TiO3-4e-→2TiO2+4Na + +O2;
[0013] Alternatively, 2Na2Ti6O 13 -4e-→12TiO2+4Na + +O2;
[0014] Or, 2Na2ZrO3-4e-→2ZrO2+4Na + +O2;
[0015] Or, 2Na2SiO3-4e-→2SiO2+4Na + +O2;
[0016] Or, 2Na2Si2O5-4e-→4SiO2+4Na + +O2;
[0017] Or, 2Na2Si3O7-4e-→6SiO2+4Na + +O2;
[0018] Or, 2Na2Si 10 O 21 -4e-→20SiO2+4Na + +O2. That is, the sodium-supplementing compound can be oxidized and decomposed to obtain sodium ions and inorganic materials during the formation or charging process.
[0019] The decomposed inorganic material has high hardness and high temperature resistance, which can improve the high temperature shrinkage performance of the diaphragm and reduce the problem of the diaphragm being punctured by dendrites.
[0020] Optionally, the diaphragm comprises a sodium-supplementing diaphragm, the sodium-supplementing diaphragm comprises the sodium-supplementing compound, and the thickness of the sodium-supplementing diaphragm ranges from 5 μm to 15 μm; preferably, from 7 μm to 13 μm;
[0021] Alternatively, the diaphragm includes a base film and a sodium-supplementing layer disposed on the base film, the sodium-supplementing layer includes the sodium-supplementing compound, and the thickness of the sodium-supplementing layer ranges from 5 μm to 15 μm; preferably, from 7 μm to 13 μm.
[0022] It can be understood that the diaphragm in the present application can be a single-layer diaphragm or a multi-layer diaphragm. When it is a single-layer diaphragm, the single-layer diaphragm is a sodium-supplemented diaphragm. For example, the sodium-supplemented diaphragm raw material (sodium-supplemented compound, polymer) is melt-extruded to obtain a sodium-supplemented diaphragm; when it is a multi-layer diaphragm, at least one layer of the multi-layer diaphragm is a sodium-supplemented diaphragm. For example, the sodium-supplemented diaphragm raw material (sodium-supplemented compound, polymer) and the base film raw material (polymer) are melt-coextruded at the same time. The prepared diaphragm includes a sodium-supplemented diaphragm composed of a sodium-supplemented compound coated with a polymer and a base film bonded to the sodium-supplemented diaphragm to form a double-layer diaphragm; the sodium-supplemented diaphragm includes a sodium-supplemented compound, and the thickness of the sodium-supplemented diaphragm ranges from 5μm to 15μm; preferably, 7μm to 13μm. It can be understood that the thickness of the above-mentioned sodium-supplemented diaphragm refers to the thickness after hot pressing.
[0023] It can also be understood that the diaphragm includes a base film and a sodium supplement layer provided on the base film, the sodium supplement layer includes a sodium supplement compound, and the thickness of the sodium supplement layer ranges from 5 μm to 15 μm; preferably, 7 μm to 13 μm. That is, the sodium supplement compound can be prepared into a slurry and coated on the base film to obtain the diaphragm, and the thickness of the sodium supplement layer ranges from 5 μm to 15 μm; preferably, 7 μm to 13 μm.
[0024] The thickness of the sodium-supplementing membrane or the sodium-supplementing layer is within the above range, which can improve the sodium-supplementing capacity of the membrane, as well as the high temperature resistance and puncture resistance of the membrane.
[0025] Optionally, the Dv50 value of the sodium supplement compound is in the range of 100 nm to 3 μm, preferably, 100 nm to 1 μm.
[0026] The Dv50 of the sodium-supplementing compound being within the above range can help decompose the sodium-supplementing compound. In addition, it can alleviate the problem of the sodium-supplementing compound being too large and clogging the micropores of the sodium-supplementing membrane, improve the problem of the sodium-supplementing compound being too small and easy to agglomerate, causing uneven distribution of the sodium-supplementing compound in the sodium-supplementing membrane, and facilitate the preparation of a sodium-supplementing membrane of appropriate thickness.
[0027] Optionally, the membrane comprises a sodium-supplementing membrane, and the sodium-supplementing membrane further comprises a polymer, and the polymer is coated on the surface of the sodium-supplementing compound.
[0028] The sodium-supplementing membrane also includes a polymer. The surface of the sodium-supplementing compound is coated with the polymer. The sodium-supplementing compound is coated with the polymer, so that the sodium-supplementing compound in the sodium-supplementing membrane is not easy to fall off from the sodium-supplementing membrane, thereby improving the sodium-supplementing effect of the membrane in the sodium secondary battery.
[0029] At the same time, considering that the sodium-supplementing compounds will be oxidatively decomposed into inorganic materials during the formation or charging process, the problem of inorganic materials being released into the electrolyte is also alleviated by polymer coating.
[0030] Optionally, the sodium supplementation membrane further comprises a toughening agent;
[0031] Alternatively, the sodium-supplementing membrane further comprises a toughening agent, and the mass percentage of the toughening agent to the mass percentage of the sodium-supplementing membrane is 5% to 15%, preferably, 5% to 10%.
[0032] In order to improve the firmness of the combination between the sodium-supplementing compound and the polymer, the sodium-supplementing membrane also includes a toughening agent. Further, the mass percentage of the toughening agent to the mass percentage of the sodium-supplementing membrane is 5% to 15%, preferably 5% to 10%.
[0033] Optionally, the sodium supplementation membrane further comprises a polymer, and the polymer comprises at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide;
[0034] And / or, the sodium supplementation membrane further comprises a toughening agent, and the toughening agent comprises at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene butadiene rubber, hydroxypropyl methylcellulose, carboxy styrene butadiene latex or polyvinyl alcohol.
[0035] The sodium supplement membrane in the present application also includes a polymer, and the polymer includes but is not limited to at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide.
[0036] The sodium-supplementing diaphragm in the present application also includes a toughening agent, which includes but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene-butadiene rubber, hydroxypropyl methylcellulose, carboxystyrene-butadiene latex or polyvinyl alcohol.
[0037] Optionally, the diaphragm further includes a non-sodium-supplementing diaphragm, and the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm.
[0038] It can be understood that the diaphragm also includes a non-sodium-supplementing diaphragm, that is, the diaphragm includes at least two layers, at least one of which is a non-sodium-supplementing diaphragm, and at least the other side is a sodium-supplementing diaphragm, and the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm.
[0039] By setting a multi-layer diaphragm, the thickness of the diaphragm can be adjusted, and the porosity of the non-sodium supplementing diaphragm can be adjusted as needed. For example, the porosity of the sodium supplementing diaphragm and the non-sodium supplementing diaphragm can be set to be different. For example, in one embodiment, the porosity of the non-sodium supplementing diaphragm is greater than the porosity of the sodium supplementing diaphragm to reduce the inorganic material in the sodium supplementing diaphragm from falling into the electrolyte, and improve the overall air permeability of the diaphragm, and improve the performance of ions passing through the diaphragm. For example, in one embodiment, the non-sodium supplementing diaphragm can be a base membrane, and the prepared sodium supplementing diaphragm can be pasted on the surface of the base membrane to form a diaphragm with at least two layers.
[0040] Optionally, the diaphragm is used to be arranged on one side of the positive electrode plate or the negative electrode plate, and the sodium-supplementing diaphragm is arranged on a side of the non-sodium-supplementing diaphragm facing the positive electrode plate.
[0041] Theoretically, the sodium-supplementing diaphragm can be arranged on any side of the non-sodium-supplementing diaphragm. Considering that the sodium-supplementing compound will undergo an oxidative decomposition reaction during the formation or charging process, the potential of the positive electrode plate is higher than that of the negative electrode plate, which is more conducive to the decomposition of the sodium-supplementing compound. Therefore, under preferred circumstances, the sodium-supplementing diaphragm is arranged on the side of the non-sodium-supplementing diaphragm facing the positive electrode plate.
[0042] Optionally, the total thickness of the diaphragm ranges from 13 μm to 30 μm; preferably, from 15 μm to 20 μm.
[0043] It can be understood that the diaphragm in the present application can be a multi-layer diaphragm. When it is a multi-layer diaphragm, at least one layer of the multi-layer diaphragm is a sodium-supplementing diaphragm. In the multi-layer diaphragm, the total thickness range of the diaphragm is 13μm to 30μm; preferably, 15μm to 20μm.
[0044] For example, the multilayer diaphragm includes a base membrane and a sodium-supplementing diaphragm disposed on at least one side of the base membrane. Providing the sodium-supplementing diaphragm on the base membrane can increase the thickness of the overall diaphragm. At the same time, the porosity of the base membrane can be greater than the porosity of the sodium-supplementing diaphragm, thereby improving the overall puncture resistance and air permeability of the diaphragm.
[0045] The base film includes an organic microporous film, and the material of the base film includes an organic polymer material, for example, polyethylene, polypropylene, etc.
[0046] The material of the base film is the same as that of the polymer.
[0047] In theory, the material of the base film and the material of the polymer can be the same or different, preferably the same, to reduce the problem of inconsistent ion conduction rates between the base film and the sodium supplementation membrane, which affects the battery performance. For example, the material of the base film includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide.
[0048] Optionally, the mass percentage of the sodium-supplementing compound to the total mass of the diaphragm is 5% to 30%, preferably 10% to 20%.
[0049] It can be understood that when the membrane is a single-layer membrane, the mass percentage of the sodium-supplementing compound to the mass of the single-layer membrane is 5% to 30%, preferably, 10% to 20%.
[0050] When the diaphragm is a multi-layer diaphragm, at least one layer is a sodium-supplementing diaphragm, and the mass percentage of the sodium-supplementing compound to the mass of the multi-layer diaphragm is 5% to 30%, preferably, 10% to 20%.
[0051] That is, by setting the mass percentage of the mass of the sodium-supplementing compound to the mass of the diaphragm within the above range, the sodium ions lost during the formation or charging process can be supplemented. It can be understood that, for example, when the mass percentage of the mass of the sodium-supplementing compound to the mass of the diaphragm is greater than 8%, the sodium-supplementing compound will not be completely decomposed in the formation stage, and there is still remaining sodium-supplementing compound to be decomposed during the circulation process to supplement the sodium loss during the circulation process.
[0052] In addition, the mass percentage of the mass of the sodium-supplementing compound to the mass of the diaphragm is set within the above range, and the inorganic material produced by the decomposition of the sodium-supplementing compound can improve the high-temperature shrinkage and puncture resistance of the diaphragm, and effectively improve the cycle performance of the battery. It can be understood that the mass of the sodium-supplementing compound to the mass of the diaphragm is set within the above range, which can improve the sodium supplement effect and improve the mass energy density of the battery. Taking all factors into consideration, the present application adopts a mass percentage of the mass of the sodium-supplementing compound to the total mass of the diaphragm of 5% to 30%, preferably 10% to 20%.
[0053] Optionally, the porosity of the membrane is in the range of 30% to 45%, preferably, 35% to 45%.
[0054] Taking into account the sodium supplementation compound decomposition to produce inorganic materials, in order to reduce the inorganic materials from falling into the electrolyte, the porosity range of the diaphragm is 30% to 45%.
[0055] Optionally, the diaphragm includes a sodium-supplementing diaphragm and a non-sodium-supplementing diaphragm, the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm, and the porosity of the sodium-supplementing diaphragm is less than or equal to the porosity of the non-sodium-supplementing diaphragm; preferably, the difference between the porosity of the non-sodium-supplementing diaphragm and the porosity of the sodium-supplementing diaphragm is less than or equal to 5%.
[0056] The porosity of the sodium-supplementing membrane and the non-sodium-supplementing membrane can be set to be the same or different. For example, in one embodiment, the porosity of the non-sodium-supplementing membrane is greater than the porosity of the sodium-supplementing membrane, so as to reduce the inorganic material in the sodium-supplementing membrane from falling into the electrolyte, improve the overall air permeability of the membrane, and improve the performance of ions passing through the membrane. When the porosities of the two are different, the porosity of the sodium-supplementing membrane is less than the porosity of the non-sodium-supplementing membrane, and the difference between the porosity of the non-sodium-supplementing membrane and the porosity of the sodium-supplementing membrane is less than or equal to 5%.
[0057] Optionally, the porosity of the sodium supplementing membrane ranges from 30% to 45%, preferably, from 35% to 45%;
[0058] And / or, the porosity of the non-sodium supplementing membrane ranges from 30% to 45%, preferably, from 37% to 45%.
[0059] The porosity of the sodium-supplementing membrane is set within the above range, which can reduce the loss of inorganic materials in the sodium-supplementing membrane into the electrolyte.
[0060] The porosity of the non-sodium supplemented diaphragm is set within the above range to improve the overall air permeability of the diaphragm and enhance the performance of ions passing through the diaphragm.
[0061] Optionally, the present application also provides a method for preparing the above-mentioned diaphragm, comprising:
[0062] Prepare the raw materials of the diaphragm, the raw materials of the diaphragm include sodium supplement compounds, the chemical formula of the sodium supplement compounds is NaAlO2, Na2M n O 2n+1 At least one of, wherein M comprises at least one of Ti, Zr, and Si, 1≤n≤10;
[0063] The raw material of the diaphragm is prepared into a diaphragm.
[0064] It is understood that, in one embodiment, the diaphragm can be a single-layer film, which can be prepared by melt extrusion technology, and the polymer is coated on the surface of the sodium-supplementing compound. That is, the raw materials of the diaphragm (sodium-supplementing compound, polymer) are added to the extruder of the diaphragm extrusion device, melt extruded, and passed through a cooling roller to obtain a composite film substrate; the composite film substrate is subjected to a cold drawing process to form holes, heat treatment and hot drawing process to form holes, and shaped to obtain a single-layer film.
[0065] In another embodiment, the diaphragm includes a base film and a sodium-supplementing layer disposed on the base film. In the step of preparing the raw materials for the diaphragm, the sodium-supplementing compound can be prepared into a slurry and coated on the base film to obtain the diaphragm.
[0066] Alternatively, in another embodiment, the diaphragm may be a multi-layer film, and a single-layer film is produced by melt extrusion technology, and the single-layer film is bonded to a base film to form a double-layer structure.
[0067] Or in another embodiment, melt co-extrusion is used to melt co-extrude the diaphragm raw material (sodium-supplementing compound, polymer) and the base film raw material (polymer) at the same time. The prepared diaphragm includes a film layer structure composed of the sodium-supplementing compound coated with a polymer and a base film bonded to the film layer structure. Melt co-extrusion refers to an extrusion process in which several extruders are used to simultaneously supply different plastic molten material flows to a composite head to merge into a multi-layer composite product.
[0068] Optionally, the process of preparing the raw material of the diaphragm into a diaphragm includes:
[0069] The raw material of the diaphragm is added into the extruder of the diaphragm extrusion device, melt-extruded, and passed through a cooling roller to obtain a composite film substrate;
[0070] The composite membrane substrate is subjected to a cold drawing process to form holes, subjected to a heat treatment and a hot drawing process to form holes, and shaped to obtain a sodium supplementing diaphragm.
[0071] The extrusion diaphragm device is used to push the diaphragm raw material to extrude the diaphragm raw material into a film.
[0072] The sodium-supplementing diaphragm prepared by melt extrusion includes a polymer-coated sodium-supplementing compound. On the one hand, the problem of inorganic materials generated by the decomposition of the sodium-supplementing compound falling off from the diaphragm into the electrolyte can be reduced. On the other hand, the problem of the sodium-supplementing compound coating on the diaphragm falling off due to insufficient adhesion during the folding and curling process when assembling the battery can be reduced, resulting in reduced sodium-supplementing efficiency. In addition, the preparation method does not involve the use of organic solvents, thereby reducing production costs and environmental pollution.
[0073] Optionally, in the step of preparing the raw material of the diaphragm, the following steps are further included:
[0074] The sodium supplement compound, the polymer and the toughening agent are stirred and mixed at a stirring speed of 400 r / min to 800 r / min and a stirring time of 0.5 h to 1 h to obtain a raw material for a diaphragm.
[0075] In the process of preparing the raw material of the diaphragm, the sodium supplement compound, the polymer and the toughening agent are stirred and mixed at a stirring speed of 400 r / min to 800 r / min and a stirring time of 0.5 h to 1 h to obtain the raw material of the diaphragm. Adding the toughening agent can improve the firmness of the combination of the sodium supplement material and the polymer, and improve the tightness of the combination of the sodium supplement diaphragm and the base membrane.
[0076] Optionally, the temperature of the cooling roller is 15°C to 30°C;
[0077] and / or, the thickness of the composite film substrate is 10 μm to 25 μm;
[0078] And / or, the cold drawing process is performed at a temperature of 15° C. to 30° C. and a stretching speed of 0.01 m / min to 0.1 m / min for uniaxial stretching;
[0079] And / or, the heat treatment condition is heating at 15°C to 30°C below the melting point of the polymer for 30min to 60min;
[0080] And / or, the conditions of the hot drawing process are uniaxial stretching at a temperature of 100° C. to 160° C., a stretching ratio of 1 to 5 times, and a stretching speed of 0.05 m / min to 0.5 m / min;
[0081] And / or, the shaping treatment conditions are: temperature 15°C to 30°C, time 0.5h to 2h.
[0082] During the preparation process of the diaphragm, the corresponding steps are made to meet the above conditions to obtain a diaphragm of suitable thickness.
[0083] Optionally, the present application further provides a battery preparation process, the battery preparation process comprising assembling a diaphragm, a positive electrode sheet, and a negative electrode sheet, the diaphragm comprising the diaphragm as described;
[0084] Alternatively, the manufacturing process of the battery includes assembling a diaphragm, a positive electrode sheet, and a negative electrode sheet, and the diaphragm includes a diaphragm prepared by the diaphragm preparation method as described above.
[0085] Optionally, during the process of assembling the separator, the positive electrode sheet, and the negative electrode sheet, the following steps are included:
[0086] The battery in which the separator is packaged with the positive electrode sheet and the negative electrode sheet is injected with liquid, and the battery is subjected to a formation treatment.
[0087] Sodium battery formation is the first charging process of the battery after the sodium battery is filled with liquid. This process can activate the active substances in the battery and activate the sodium battery.
[0088] Considering that the sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the formation process, for this purpose, the battery after the diaphragm is packaged with the positive electrode plate and the negative electrode plate is injected with liquid, and the battery is subjected to a formation treatment, so that the sodium-supplementing compound in the diaphragm can be decomposed, and the product sodium ions can replenish the sodium ions consumed during the formation or charging process, and the product inorganic materials can improve the high-temperature shrinkage and puncture resistance of the diaphragm, thereby effectively improving the cycle performance of the battery.
[0089] Optionally, in the step of performing a formation treatment on the battery, the voltage range of the formation is 3V to 4.2V;
[0090] And / or, the formation temperature is 45°C to 80°C;
[0091] And / or, the formation time is 2h to 5h;
[0092] And / or, the vacuum degree of the formed battery ranges from 0.01 MPa to 0.1 MPa.
[0093] Using the above voltage range during the formation process helps to decompose the sodium-supplementing compound.
[0094] In the above formation temperature range, the decomposition rate of the sodium supplement compound can be increased.
[0095] Within the above formation time range, the sodium ions lost in the formation stage can be effectively replenished.
[0096] The above-mentioned vacuum degree is set inside the battery during the formation process to remove the gas generated during the decomposition process of the sodium-supplementing compound.
[0097] In addition, setting the vacuum degree of the battery to the above vacuum degree can reduce the loss of electrolyte and alleviate the problem of inorganic materials generated during the decomposition of the sodium-supplementing compound being brought into the electrolyte from the polymer pores.
[0098] Optionally, after the step of performing formation treatment on the battery, the step further includes charging the battery, and the charging voltage range is 3V to 4.2V.
[0099] Considering that the sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the charging process, setting the charging voltage range value in the above range during the charging process can facilitate the decomposition of the sodium-supplementing compound.
[0100] That is, the sodium-supplementing compound of the present application will not only decompose in the formation stage, which helps to supplement the sodium ions in the formation stage, but also decompose during the battery charging process to achieve the sodium ion supplementation during the cycle process.
[0101] The present application also provides a battery, which includes a battery prepared by the battery preparation process as described above.
[0102] The present application also provides an electrical device, which includes the battery as described above.
[0103] The membrane of the present application comprises a sodium supplement compound, the chemical formula of which is NaAlO2, Na2M n O 2n+1At least one of, wherein M includes at least one of Ti, Zr, and Si, and 1≤n≤10. The above-mentioned sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the formation or charging process. The product sodium ions can replenish the sodium ions consumed during the formation or charging process, and the product inorganic materials can improve the high-temperature shrinkage and puncture resistance of the diaphragm, effectively improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0104] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0105] Figure 1 A schematic diagram of the structure of a diaphragm according to an embodiment of the present application;
[0106] Figure 2 A schematic diagram of the structure of a diaphragm according to an embodiment of the present application;
[0107] Figure 3 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0108] Figure 4 yes Figure 3 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0109] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application;
[0110] Figure 6 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0111] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0112] Figure 8 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.
[0113] Description of Figure Numbers:
[0114] Label name Label name 100 Diaphragm 4 Battery Module 10 Sodium supplement diaphragm 5 Battery Cell 20 Non-sodium supplemented diaphragm 51 case 1 Battery Pack 52 Electrode assembly 2 Upper box 53 Cover 3 Lower box
[0115] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0116] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0117] Hereinafter, the diaphragm and its preparation method, the preparation process of the battery, the battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0118] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0119] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0120] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0121] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0122] Compared with lithium secondary batteries with scarce elements such as lithium, cobalt and nickel, sodium secondary batteries have the advantages of abundant sodium resources and low raw material costs, which makes sodium secondary batteries have great development prospects in the field of energy storage.
[0123] There is a problem of sodium loss during the cycle of sodium secondary batteries.
[0124] For example, due to some irreversible reactions such as the formation of the solid electrolyte membrane (SEI membrane) on the negative electrode surface during the initial charge and discharge formation process, the positive electrode material will experience sodium ion loss, which will lead to a decrease in the energy density of the sodium secondary battery.
[0125] In order to solve the above technical problems, the present application provides a separator, aiming to improve the performance of sodium secondary batteries.
[0126] The membrane includes a sodium-supplementing compound, the chemical formula of which is NaAlO2, Na2M n O 2n+1 At least one of, wherein M includes at least one of Ti, Zr, and Si, and 1≤n≤10.
[0127] Diaphragm, in the structure of secondary battery, diaphragm is one of the key internal components. The performance of diaphragm determines the interface structure and internal resistance of the battery, directly affecting the battery's capacity, cycle and safety performance. Excellent performance diaphragm plays an important role in improving the comprehensive performance of the battery. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through.
[0128] The above-mentioned sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the formation or charging process. The product sodium ions can replenish the sodium ions consumed during the formation or charging process, and the product inorganic materials can improve the high-temperature shrinkage and puncture resistance of the diaphragm, thereby effectively improving the cycle performance of the battery.
[0129] In the above 1≤n≤10, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, etc., and the range values between any two of the above point values.
[0130] In one embodiment, 1≤n≤5.
[0131] Sodium supplement compound Na2M n O 2n+1 In the range of 1≤n≤5, sodium supplement compounds with n in the above range are relatively common in nature, easy to obtain and relatively low in cost.
[0132] In the above 1≤n≤5, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1, 2, 3, 4, 5, etc., and the range values between any two of the above point values.
[0133] In one embodiment, Na2M n O 2n+1 Including Na2TiO3, Na2Ti2O5, Na2Ti5O 11 、Na2Ti6O 13 , Na2ZrO3, Na2SiO3, Na2Si2O5, Na2Si3O7, Na2Si5O 11 、Na2Si 10 O 21 At least one of .
[0134] Na2M in this application n O 2n+1 Including but not limited to Na2TiO3, Na2Ti2O5, Na2Ti5O 11 、Na2Ti6O 13 , Na2ZrO3, Na2SiO3, Na2Si2O5, Na2Si3O7, Na2Si5O 11 、Na2Si 10 O 21 It is understandable that the sodium supplement compound can be oxidized and decomposed during the formation or charging process to obtain sodium ions and inorganic materials.
[0135] For example, 4NaAlO2-4e-→2Al2O3+4Na + +O2; or, 2Na2TiO3-4e-→2TiO2+4Na + +O2; or, 2Na2Ti6O 13 -4e-→12TiO2+4Na ++O2; or, 2Na2ZrO3-4e-→2ZrO2+4Na + +O2; or, 2Na2SiO3-4e-→2SiO2+4Na + +O2; or, 2Na2Si2O5-4e-→4SiO2+4Na + +O2; or, 2Na2Si3O7-4e-→6SiO2+4Na + +O2; or, 2Na2Si 10 O 21 -4e-→20SiO2+4Na + +O2. That is, the sodium-supplementing compound can be oxidized and decomposed to obtain sodium ions and inorganic materials during the formation or charging process.
[0136] The decomposed inorganic material has high hardness and high temperature resistance, which can improve the high temperature shrinkage performance of the diaphragm and reduce the problem of the diaphragm being punctured by dendrites.
[0137] In one embodiment, the diaphragm includes a sodium-supplemented diaphragm, the sodium-supplemented diaphragm includes a sodium-supplemented compound, and the thickness of the sodium-supplemented diaphragm ranges from 5μm to 15μm; preferably, 7μm to 13μm; or, the diaphragm includes a base film and a sodium-supplemented layer provided on the base film, the sodium-supplemented layer includes a sodium-supplemented compound, and the thickness of the sodium-supplemented layer ranges from 5μm to 15μm; preferably, 7μm to 13μm.
[0138] It is understandable that if Figure 1 and Figure 2 , the diaphragm 100 in the present application can be a single-layer diaphragm or a multi-layer diaphragm. When it is a single-layer diaphragm, the single-layer diaphragm is a sodium-supplemented diaphragm 10. For example, the sodium-supplemented diaphragm raw material (sodium-supplemented compound, polymer) is melt-extruded to obtain a sodium-supplemented diaphragm; when it is a multi-layer diaphragm, for example, the sodium-supplemented diaphragm raw material (sodium-supplemented compound, polymer) and the base film raw material (polymer) are melt-coextruded at the same time, and the prepared diaphragm includes a sodium-supplemented diaphragm composed of a sodium-supplemented compound coated with a polymer and a base film bonded to the sodium-supplemented diaphragm to form a double-layer diaphragm; at least one layer of the multi-layer diaphragm is a sodium-supplemented diaphragm 10, and the sodium-supplemented diaphragm 10 includes a sodium-supplemented compound, and the thickness of the sodium-supplemented diaphragm ranges from 5μm to 15μm; preferably, 7μm to 13μm. It can be understood that the thickness of the above-mentioned sodium-supplemented diaphragm refers to the thickness after hot pressing.
[0139] It can also be understood that the diaphragm includes a base film and a sodium supplement layer provided on the base film, the sodium supplement layer includes a sodium supplement compound, and the thickness of the sodium supplement layer ranges from 5 μm to 15 μm; preferably, 7 μm to 13 μm. That is, the sodium supplement compound can be prepared into a slurry and coated on the base film to obtain the diaphragm, and the thickness of the sodium supplement layer ranges from 5 μm to 15 μm; preferably, 7 μm to 13 μm.
[0140] The thickness of the sodium-supplementing membrane or the sodium-supplementing layer is within the above range, which can improve the sodium-supplementing capacity of the membrane, as well as the high temperature resistance and puncture resistance of the membrane.
[0141] In the above-mentioned 5μm to 15μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc., and the range values between any two of the above-mentioned point values.
[0142] In the above-mentioned 7μm to 13μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, etc., as well as the range values between any two of the above-mentioned point values.
[0143] In one embodiment, the Dv50 value of the sodium supplementing compound is in the range of 100 nm to 3 μm, preferably, 100 nm to 1 μm.
[0144] Dv50 is the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. Dv50 is also called the median diameter or median particle size. Dv50 is often used to indicate the average particle size of powders.
[0145] Dv50 can be tested by methods known in the art. For example, GB / T19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as a Malvern Mastersizer-3000 or other instrument.
[0146] The Dv50 of the sodium-supplementing compound being within the above range can help decompose the sodium-supplementing compound. In addition, it can alleviate the problem of the sodium-supplementing compound being too large and clogging the micropores of the sodium-supplementing membrane, improve the problem of the sodium-supplementing compound being too small and easy to agglomerate, causing uneven distribution of the sodium-supplementing compound in the sodium-supplementing membrane, and facilitate the preparation of a sodium-supplementing membrane of appropriate thickness.
[0147] In the above-mentioned 100nm to 3μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 500nm, 550nm, 800nm, 850nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, etc., as well as the range values between any two of the above-mentioned point values.
[0148] In the above-mentioned 100nm to 1μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1μm, etc., and the range value between any two of the above-mentioned point values.
[0149] In one embodiment, the membrane includes a sodium-supplementing membrane, and the sodium-supplementing membrane further includes a polymer, and the polymer is coated on the surface of the sodium-supplementing compound.
[0150] Polymer, a polymer refers to a high molecular weight compound composed of many identical, simple structural units repeatedly connected by covalent bonds, such as polyethylene, polypropylene, etc.
[0151] The polymer is coated on the surface of the sodium-supplementing compound, which means that the sodium-supplementing compound in the sodium-supplementing membrane is coated by the polymer, thereby reducing direct exposure of the sodium-supplementing compound to the outside.
[0152] The sodium-supplementing membrane also includes a polymer. The surface of the sodium-supplementing compound is coated with the polymer. The sodium-supplementing compound is coated with the polymer, so that the sodium-supplementing compound in the sodium-supplementing membrane is not easy to fall off from the sodium-supplementing membrane, thereby improving the sodium-supplementing effect of the membrane in the sodium secondary battery.
[0153] At the same time, considering that the sodium-supplementing compounds will be oxidatively decomposed into inorganic materials during the formation or charging process, the problem of inorganic materials being released into the electrolyte is also alleviated by polymer coating.
[0154] In one embodiment, the sodium-supplementing membrane further includes a toughening agent; or, the sodium-supplementing membrane further includes a toughening agent, and the mass percentage of the toughening agent to the mass percentage of the sodium-supplementing membrane is 5% to 15%, preferably, 5% to 10%.
[0155] In order to improve the firmness of the combination between the sodium-supplementing compound and the polymer, the sodium-supplementing membrane also includes a toughening agent. Further, the mass percentage of the toughening agent to the mass percentage of the sodium-supplementing membrane is 5% to 15%, preferably 5% to 10%.
[0156] In the above 5% to 15%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., and the range values between any two of the above point values.
[0157] In the above 5% to 10%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5%, 6%, 7%, 8%, 9%, 10%, etc., and the range values between any two of the above point values.
[0158] In one embodiment, the sodium-supplementing membrane further includes a polymer, which includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide; and / or, the sodium-supplementing membrane further includes a toughening agent, which includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene-butadiene rubber, hydroxypropyl methylcellulose, carboxystyrene-butadiene latex, or polyvinyl alcohol.
[0159] The sodium supplement membrane in the present application also includes a polymer, and the polymer includes but is not limited to at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide.
[0160] The sodium-supplementing diaphragm in the present application also includes a toughening agent, which includes but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene-butadiene rubber, hydroxypropyl methylcellulose, carboxystyrene-butadiene latex or polyvinyl alcohol.
[0161] In one embodiment, the diaphragm further comprises a non-sodium-compensating diaphragm, and the sodium-compensating diaphragm is disposed on at least one side of the non-sodium-compensating diaphragm.
[0162] Non-sodium supplementing membranes do not include sodium supplementing compounds.
[0163] For example, Figure 2 As shown, the membrane 100 includes a sodium-supplementing membrane 10 and a non-sodium-supplementing membrane 20 .
[0164] It can be understood that the diaphragm also includes a non-sodium-supplementing diaphragm, that is, the diaphragm includes at least two layers, at least one of which is a non-sodium-supplementing diaphragm, and at least the other side is a sodium-supplementing diaphragm, and the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm.
[0165] By setting a multi-layer diaphragm, the thickness of the diaphragm can be adjusted, and the porosity of the non-sodium supplementing diaphragm can be adjusted as needed. For example, the porosity of the sodium supplementing diaphragm and the non-sodium supplementing diaphragm can be set to be different. For example, in one embodiment, the porosity of the non-sodium supplementing diaphragm is greater than the porosity of the sodium supplementing diaphragm to reduce the inorganic material in the sodium supplementing diaphragm from falling into the electrolyte, and improve the overall air permeability of the diaphragm, and improve the performance of ions passing through the diaphragm. For example, in one embodiment, the non-sodium supplementing diaphragm can be a base membrane, and the prepared sodium supplementing diaphragm can be pasted on the surface of the base membrane to form a diaphragm with at least two layers.
[0166] In one embodiment, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the sodium-supplementing diaphragm is arranged on the side of the non-sodium-supplementing diaphragm facing the positive electrode sheet.
[0167] It is understandable that in the process of preparing the battery, the diaphragm and the electrode plates need to be stacked in sequence. In the process of stacking the diaphragm and the electrode plates, the position of the diaphragm in the electrode plates can be set as needed. For example, the diaphragm can be set between the positive electrode plate and the negative electrode plate.
[0168] Theoretically, the sodium-supplementing diaphragm can be arranged on any side of the non-sodium-supplementing diaphragm. Considering that the sodium-supplementing compound will undergo an oxidative decomposition reaction during the formation or charging process, the potential of the positive electrode plate is higher than that of the negative electrode plate, which is more conducive to the decomposition of the sodium-supplementing compound. Therefore, under preferred circumstances, the sodium-supplementing diaphragm is arranged on the side of the non-sodium-supplementing diaphragm facing the positive electrode plate.
[0169] In one embodiment, the total thickness of the membrane is in the range of 13 μm to 30 μm; preferably, 15 μm to 20 μm.
[0170] It can be understood that the diaphragm in the present application can be a multi-layer diaphragm. When it is a multi-layer diaphragm, at least one layer of the multi-layer diaphragm is a sodium-supplementing diaphragm. In the multi-layer diaphragm, the total thickness range of the diaphragm is 13μm to 30μm; preferably, 15μm to 20μm.
[0171] For example, the multilayer diaphragm includes a base membrane and a sodium-supplementing diaphragm disposed on at least one side of the base membrane. Providing the sodium-supplementing diaphragm on the base membrane can increase the thickness of the overall diaphragm. At the same time, the porosity of the base membrane can be greater than the porosity of the sodium-supplementing diaphragm, thereby improving the overall puncture resistance and air permeability of the diaphragm.
[0172] The base film includes an organic microporous film, and the material of the base film includes an organic polymer material, for example, polyethylene, polypropylene, etc.
[0173] The material of the base film is the same as that of the polymer.
[0174] In theory, the material of the base film and the material of the polymer can be the same or different, preferably the same, to reduce the problem of inconsistent ion conduction rates between the base film and the sodium supplementation membrane, which affects the battery performance. For example, the material of the base film includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide.
[0175] In the above-mentioned 13μm to 30μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiment and 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, etc., and the range value between any two of the above-mentioned point values.
[0176] In the above-mentioned 15μm to 20μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, etc., and the range values between any two of the above-mentioned point values.
[0177] In one embodiment, the mass percentage of the sodium supplement compound to the total mass of the membrane is 5% to 30%, preferably, 10% to 20%.
[0178] It can be understood that when the membrane is a single-layer membrane, the mass percentage of the sodium-supplementing compound to the mass of the single-layer membrane is 5% to 30%, preferably, 10% to 20%.
[0179] When the diaphragm is a multi-layer diaphragm, at least one layer is a sodium-supplementing diaphragm, and the mass percentage of the sodium-supplementing compound to the mass of the multi-layer diaphragm is 5% to 30%, preferably, 10% to 20%.
[0180] That is, by setting the mass percentage of the mass of the sodium-supplementing compound to the mass of the diaphragm within the above range, the sodium ions lost during the formation or charging process can be supplemented. It can be understood that, for example, when the mass percentage of the mass of the sodium-supplementing compound to the mass of the diaphragm is greater than 8%, the sodium-supplementing compound will not be completely decomposed in the formation stage, and there is still remaining sodium-supplementing compound to be decomposed during the circulation process to supplement the sodium loss during the circulation process.
[0181] In addition, the mass percentage of the mass of the sodium-supplementing compound to the mass of the diaphragm is set within the above range, and the inorganic material produced by the decomposition of the sodium-supplementing compound can improve the high-temperature shrinkage and puncture resistance of the diaphragm, and effectively improve the cycle performance of the battery. It can be understood that the mass of the sodium-supplementing compound to the mass of the diaphragm is set within the above range, which can improve the sodium supplement effect and improve the mass energy density of the battery. Taking all factors into consideration, the present application adopts a mass percentage of the mass of the sodium-supplementing compound to the total mass of the diaphragm of 5% to 30%, preferably 10% to 20%.
[0182] In the above 5% to 30%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc., and the range values between any two of the above point values.
[0183] In the above 10% to 20%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., and the range values between any two of the above point values.
[0184] In one embodiment, the porosity of the membrane is in the range of 30% to 45%, preferably, 35% to 45%.
[0185] Taking into account the sodium supplementation compound decomposition to produce inorganic materials, in order to reduce the inorganic materials from falling into the electrolyte, the porosity range of the diaphragm is 30% to 45%.
[0186] In the above 30% to 45%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc., and the range values between any two of the above point values.
[0187] In the above 35% to 45%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc., and the range values between any two of the above point values.
[0188] In one embodiment, the diaphragm includes a sodium-supplementing diaphragm and a non-sodium-supplementing diaphragm, the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm, and the porosity of the sodium-supplementing diaphragm is less than or equal to the porosity of the non-sodium-supplementing diaphragm.
[0189] The porosity of the sodium-supplementing membrane and the non-sodium-supplementing membrane can be set to be the same or different. For example, in one embodiment, the porosity of the non-sodium-supplementing membrane is greater than the porosity of the sodium-supplementing membrane, so as to reduce the inorganic material in the sodium-supplementing membrane from falling into the electrolyte, improve the overall air permeability of the membrane, and improve the performance of ions passing through the membrane. When the porosities of the two are different, the porosity of the sodium-supplementing membrane is less than the porosity of the non-sodium-supplementing membrane, and the difference between the porosity of the non-sodium-supplementing membrane and the porosity of the sodium-supplementing membrane is less than or equal to 5%.
[0190] In one embodiment, the porosity of the sodium-supplementing membrane ranges from 30% to 45%, preferably, from 35% to 45%; and / or the porosity of the non-sodium-supplementing membrane ranges from 30% to 45%, preferably, from 37% to 45%.
[0191] The porosity of the sodium-supplementing membrane is set within the above range, which can reduce the loss of inorganic materials in the sodium-supplementing membrane into the electrolyte.
[0192] The porosity of the non-sodium supplemented diaphragm is set within the above range to improve the overall air permeability of the diaphragm and enhance the performance of ions passing through the diaphragm.
[0193] In the above 30% to 45%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc., and the range values between any two of the above point values.
[0194] In the above 35% to 45%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc., and the range values between any two of the above point values.
[0195] In the above 37% to 45%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc., as well as the range values between any two of the above point values.
[0196] In one embodiment, the present application also provides a method for preparing the above diaphragm, comprising: preparing a raw material for the diaphragm, the raw material for the diaphragm comprising a sodium supplement compound, the chemical formula of the sodium supplement compound being NaAlO2, Na2M n O 2n+1 At least one of the following, wherein M includes at least one of Ti, Zr, and Si, and 1≤n≤10; preparing the raw material of the diaphragm into a diaphragm.
[0197] It is understood that, in one embodiment, the diaphragm can be a single-layer film, which can be prepared by melt extrusion technology, and the polymer is coated on the surface of the sodium-supplementing compound. That is, the raw materials of the diaphragm (sodium-supplementing compound, polymer) are added to the extruder of the diaphragm extrusion device, melt extruded, and passed through a cooling roller to obtain a composite film substrate; the composite film substrate is subjected to a cold drawing process to form holes, heat treatment and hot drawing process to form holes, and shaped to obtain a single-layer film.
[0198] In another embodiment, the diaphragm includes a base film and a sodium-supplementing layer disposed on the base film. In the step of preparing the raw materials for the diaphragm, the sodium-supplementing compound can be prepared into a slurry and coated on the base film to obtain the diaphragm.
[0199] Alternatively, in another embodiment, the diaphragm may be a multi-layer film, and a single-layer film is produced by melt extrusion technology, and the single-layer film is bonded to a base film to form a double-layer structure.
[0200] Or in another embodiment, melt co-extrusion is used to melt co-extrude the diaphragm raw material (sodium-supplementing compound, polymer) and the base film raw material (polymer) at the same time. The prepared diaphragm includes a film layer structure composed of the sodium-supplementing compound coated with a polymer and a base film bonded to the film layer structure. Melt co-extrusion refers to an extrusion process in which several extruders are used to simultaneously supply different plastic molten material flows to a composite head to merge into a multi-layer composite product.
[0201] In one embodiment, the process of preparing the raw material of the diaphragm into the diaphragm includes: adding the raw material of the diaphragm into an extruder of a diaphragm extrusion device, performing melt extrusion, and obtaining a composite membrane substrate through a cooling roller; performing a cold drawing process on the composite membrane substrate to form holes, performing heat treatment and hot drawing processes to form holes, and shaping to obtain a sodium-supplementing diaphragm.
[0202] The extrusion diaphragm device is used to push the diaphragm raw material to extrude the diaphragm raw material into a film.
[0203] The sodium-supplementing diaphragm prepared by melt extrusion includes a polymer-coated sodium-supplementing compound. On the one hand, the problem of inorganic materials generated by the decomposition of the sodium-supplementing compound falling off from the diaphragm into the electrolyte can be reduced. On the other hand, the problem of the sodium-supplementing compound coating on the diaphragm falling off due to insufficient adhesion during the folding and curling process when assembling the battery can be reduced, resulting in reduced sodium-supplementing efficiency. In addition, the preparation method does not involve the use of organic solvents, thereby reducing production costs and environmental pollution.
[0204] It can be understood that the preparation principle of the melt extrusion / stretching / heat setting method is that the polymer melt crystallizes under a high stress field to form a lamella structure perpendicular to the extrusion direction and arranged in parallel, and then the elastic material is obtained by heat treatment. After the hard elastic polymer film is stretched, the lamellae are separated and a large number of microfibers appear, thereby forming a large number of microporous structures, and then the microporous film is obtained by heat setting.
[0205] In one embodiment, the step of preparing the raw material for the diaphragm also includes: stirring and mixing the sodium supplement compound, the polymer, and the toughening agent, with the stirring speed being 400 r / min to 800 r / min and the stirring time being 0.5 h to 1 h to obtain the raw material for the diaphragm.
[0206] In the process of preparing the raw material of the diaphragm, the sodium-supplementing compound, the polymer and the toughening agent are stirred and mixed at a stirring speed of 400 r / min to 800 r / min and a stirring time of 0.5 h to 1 h to obtain the raw material of the sodium-supplementing diaphragm. Adding the toughening agent can improve the firmness of the combination of the sodium-supplementing material and the polymer, and improve the tightness of the combination of the sodium-supplementing diaphragm and the base film.
[0207] In the above-mentioned 400r / min to 800r / min, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, etc., and the range values between any two of the above-mentioned point values.
[0208] In the above .5h to 1h, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, etc., as well as the range values between any two of the above point values.
[0209] In one embodiment, the temperature of the cooling roller is 15°C to 30°C; and / or, the thickness of the composite film substrate is 10μm to 25μm; and / or, the temperature of the cold drawing process is 15°C to 30°C, and the uniaxial stretching is performed at a stretching speed of 0.01m / min to 0.1m / min; and / or, the heat treatment conditions are heating at 15°C to 30°C below the melting point of the polymer for 30min to 60min; and / or, the hot drawing process conditions are uniaxial stretching at a temperature of 100°C to 160°C, a stretching ratio of 1 to 5 times, and a stretching speed of 0.05m / min to 0.5m / min; and / or, the shaping treatment conditions are: temperature 15°C to 30°C, time 0.5h to 2h.
[0210] It can be understood that the heat treatment conditions are heating at 15°C to 30°C below the melting point of the polymer for 30min to 60min. Assuming the melting point of the polymer is 100°C, the heat treatment temperature is 70°C to 85°C and the heating time is 30min to 60min.
[0211] During the preparation process of the diaphragm, the corresponding steps are made to meet the above conditions to obtain a diaphragm of suitable thickness.
[0212] In one embodiment, the present application also provides a battery preparation process, the battery preparation process includes assembling a diaphragm, a positive electrode sheet, and a negative electrode sheet, and the diaphragm includes the diaphragm as described above; or, the battery preparation process includes assembling a diaphragm, a positive electrode sheet, and a negative electrode sheet, and the diaphragm includes a diaphragm prepared by the diaphragm preparation method as described above.
[0213] In one embodiment, the process of assembling the separator, the positive electrode sheet, and the negative electrode sheet includes: injecting liquid into the battery after the separator, the positive electrode sheet, and the negative electrode sheet are packaged, and performing a formation treatment on the battery.
[0214] Sodium battery formation is the first charging process of the battery after the sodium battery is filled with liquid. This process can activate the active substances in the battery and activate the sodium battery.
[0215] Considering that the sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the formation process, for this purpose, the battery after the diaphragm is packaged with the positive electrode plate and the negative electrode plate is injected with liquid, and the battery is subjected to a formation treatment, so that the sodium-supplementing compound in the diaphragm can be decomposed, and the product sodium ions can replenish the sodium ions consumed during the formation or charging process, and the product inorganic materials can improve the high-temperature shrinkage and puncture resistance of the diaphragm, thereby effectively improving the cycle performance of the battery.
[0216] In one embodiment, in the step of performing a formation treatment on the battery, the formation voltage ranges from 3V to 4.2V; and / or the formation temperature is 45°C to 80°C; and / or the formation time is 2h to 5h; and / or the vacuum degree of the formed battery ranges from 0.01MPa to 0.1MPa.
[0217] Using the above voltage range during the formation process helps to decompose the sodium-supplementing compound.
[0218] In the above formation temperature range, the decomposition rate of the sodium supplement compound can be increased.
[0219] Within the above formation time range, the sodium ions lost in the formation stage can be effectively replenished.
[0220] The above-mentioned vacuum degree is set inside the battery during the formation process to remove the gas generated during the decomposition process of the sodium-supplementing compound.
[0221] In addition, setting the vacuum degree of the battery to the above vacuum degree can reduce the loss of electrolyte and alleviate the problem of inorganic materials generated during the decomposition of the sodium-supplementing compound being brought into the electrolyte from the polymer pores.
[0222] In the above 3V to 4.2V, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 3V, 3.2V, 3.5V, 3.8V, 4.0V, 4.2V, etc., and the range values between any two of the above point values.
[0223] In the above-mentioned 45℃ value 80℃, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, etc., as well as the range values between any two of the above-mentioned point values.
[0224] In the above 2h to 5h, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc., and the range values between any two of the above point values.
[0225] In the above-mentioned 0.01MPa to 0.1MPa, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.01MPa, 0.02MPa, 0.03MPa, 0.04MPa, 0.05MPa, 0.06MPa, 0.07MPa, 0.08MPa, 0.09MPa, 0.1MPa, etc., as well as the range values between any two of the above-mentioned point values.
[0226] In one embodiment, after the step of performing formation treatment on the battery, the step further includes charging the battery, and the charging voltage range is 3V to 4.2V.
[0227] Considering that the sodium-supplementing compound in the present application can be decomposed to obtain sodium ions and inorganic materials during the charging process, setting the charging voltage range value in the above range during the charging process can facilitate the decomposition of the sodium-supplementing compound.
[0228] That is, the sodium-supplementing compound of the present application will not only decompose in the formation stage, which helps to supplement the sodium ions in the formation stage, but also decompose during the battery charging process to achieve the sodium ion supplementation during the cycle process.
[0229] In the above 3V to 4.2V, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values, and specific examples include but are not limited to the point values in the embodiment and 3V, 3.2V, 3.5V, 3.8V, 4.0V, 4.2V, etc., and the range values between any two of the above point values. In one embodiment, the present application also provides a battery, the battery including a battery prepared by the above-mentioned battery preparation process.
[0230] In one embodiment, the present application further provides an electrical device, which includes the battery as described above.
[0231] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0232] In addition, the battery (battery cell, battery module, battery pack) and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0233] In one embodiment of the present application, a battery cell is provided.
[0234] Typically, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.
[0235] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.
[0236] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0237] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0238] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0239] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0240] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0241] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.
[0242] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0243] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0244] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0245] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0246] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0247] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0248] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0249] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0250] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0251] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0252] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0253] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0254] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0255] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.
[0256] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0257] In some embodiments, a battery cell pool may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0258] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0259] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0260] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0261] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0262] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0263] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0264] Figure 8The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.
[0265] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery cell may be used as a power source.
[0266] Example
[0267] Example 1
[0268] Preparation of diaphragm:
[0269] The sodium-supplementing compound NaAlO2 with an average particle size of 200 nm, polypropylene, and toughening agent PVDF are pre-mixed in a planetary mixer at a mass ratio of 15:75:10 at a speed of 600 r / min for 40 minutes; the mixture is added to a diaphragm extrusion device for melt extrusion, and passed through a cooling roller at a temperature of 25°C to obtain a composite membrane substrate with a thickness of 20 μm; the composite membrane substrate is subjected to a unidirectional cold drawing process at a temperature of 20°C and a stretching speed of 0.08 m / min, and then heated at 130°C for 40 minutes for heat treatment, followed by unidirectional hot drawing at a temperature of 130°C and a stretching speed of 0.35 m / min, and finally formed at a temperature of 23°C for 1 hour to obtain a diaphragm with a thickness of 13 μm.
[0270] Preparation of the battery:
[0271] Na3V2(PO4)2F3 positive electrode active material, polyvinylidene fluoride (PVDF) and conductive agent acetylene black are dispersed and dissolved in N-methylpyrrolidone (NMP) solvent in a mass ratio of 90:5:5, and evenly coated on the Al foil current collector as the positive electrode sheet. Artificial graphite material is used as the negative electrode. The electrolyte is selected as NaPF6+EMC+EC system and assembled with the above-mentioned diaphragm into a full battery.
[0272] Preparation of positive electrode
[0273] The Na3V2(PO4)2F3 positive electrode active material, the titanium-doped carbon-coated sodium orthosilicate material, the binder PVDF and the conductive agent acetylene black are dispersed and dissolved in NMP solvent in a mass ratio of 88:2:5:5 to form a uniformly dispersed slurry, and then the slurry is evenly coated on the aluminum foil current collector, and then dried, cold pressed and cut to obtain the positive electrode sheet.
[0274] Preparation of negative electrode
[0275] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a weight ratio of 96.2:0.8:0.8:1.2, and the mixture is evenly mixed to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0276] Preparation of electrolyte
[0277] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3 / 7, 12.5% NaPF6 sodium salt was added and dissolved in the organic solvent, and stirred evenly.
[0278] Preparation of sodium ion batteries
[0279] The positive electrode sheet, the separator, and the negative electrode sheet of Example 1 are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 100°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of standing, hot and cold pressing, forming (the voltage during the forming process is 3.4V, the forming temperature is 69°C, the forming time is 3.5h, and the vacuum degree of the formed battery is 0.05MPa), shaping, capacity testing, etc., to obtain the sodium ion battery product of Example 1.
[0280] Example 2
[0281] Except that the mass ratio of 15:75:10 is changed to 20:70:10, the other steps of Example 2 are the same as those of Example 1.
[0282] Example 3
[0283] The other steps of Example 4 are the same as those of Example 1, except that the cold drawing and hot drawing processes are changed to a cold drawing stretching rate of 0.05 m / min and a hot drawing stretching rate of 0.20 m / min, and the thickness of the diaphragm obtained by final shaping is 18 μm.
[0284] Example 4 and Example 5
[0285] Based on Example 1, the thickness of the separator was adjusted.
[0286] Example 6 to Example 12
[0287] On the basis of Example 1, the type of sodium supplementing compound was adjusted.
[0288] Example 13 and Example 14
[0289] On the basis of Example 1, the proportions of the sodium supplementing compound, the polymer and the toughening agent were adjusted.
[0290] Example 15 to Example 17
[0291] Based on Example 1, the Dv50 of the sodium supplementing compound was adjusted.
[0292] Example 18 and Example 19
[0293] On the basis of Example 1, the types of polymer and toughening agent were adjusted.
[0294] Embodiment 20
[0295] NaAlO2 and Ketjen black were mixed in a mass ratio of 85:15 as a solute, and N-methylpyrrolidone (NMP) with the same mass as the solute was added to prepare a slurry, and the slurry was coated on the surface of a 10 μm polypropylene base film to form a sodium supplement layer with a coating thickness of 3 μm to form a diaphragm containing a sodium supplement layer. Except for the different diaphragms, the remaining steps for assembling the full battery were the same as those in Example 1.
[0296] Comparative Example 1
[0297] On the basis of Example 1, there is no sodium supplement compound in the diaphragm, and a polypropylene film is used as the diaphragm.
[0298] Performance Testing
[0299] Diaphragm firmness test:
[0300] Using a type I tester, the prepared diaphragm sample was placed on a copper shaft with a diameter of 2 mm, and the bending performance test was performed at a speed of 180° / s for 100 seconds. The sodium supplement layer that fell off was collected and weighed to calculate the shedding rate, which was divided into the following five levels: A, shedding rate ≤ 3%, basically no shedding; B, shedding rate between 3% and 6%; C, shedding rate between 6% and 10%; D, shedding rate between 10% and 20%; E, shedding rate greater than 20%. The experiment was conducted with reference to the standard GB / T 6742-2007 (bending test for paints and varnishes).
[0301] Thermal shrinkage performance test of diaphragm:
[0302] With reference to the standard ISO 14616-1997 "Heat-shrinkable films of polyethylene, ethylene copolymers and mixtures thereof - Determination of shrinkage stress", the sample was cut into 15 mm × 130 mm strips using the FST-02 film heat shrinkage tester, and the heat shrinkage of the diaphragm heat-treated at 130°C for 30 minutes was tested.
[0303] Battery performance test
[0304] Battery capacity retention test
[0305] Taking Example 1 as an example, the battery capacity retention rate test process is as follows: at 25°C, the battery corresponding to Example 1 is charged to 4.3V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4.3V, left for 5 minutes, and then discharged to 2.8V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. Then, the battery capacity retention rate Pn after each cycle is Cn / C0*100%. In this test process, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and ... the 200th cycle corresponds to n=200. The battery capacity retention rate data corresponding to the embodiments and comparative examples in Tables 1 and 2 are the data measured after 500 cycles under the above test conditions, that is, the value of P500.
[0306] Table 1 Diaphragm parameter list
[0307]
[0308]
[0309] Table 2 Performance of diaphragm and corresponding sodium ion battery
[0310]
[0311] As can be seen from the above table, by comparing the examples with the comparative examples, the sodium-supplementing compound is added to the diaphragm, and the cycle performance of the battery is improved. By comparing Examples 1 to 19 with Example 20, Examples 1 to 19 are diaphragms prepared by using an extrusion diaphragm device, and Example 20 is a diaphragm prepared by coating the sodium-supplementing compound into a slurry. The diaphragm prepared by the extrusion diaphragm device has a battery cycle performance that is better than that of Example 20.
[0312] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A diaphragm, characterized in that: The diaphragm includes a sodium supplement compound, the chemical formula of which is NaAlO2, Na2M n O 2n+1 At least one of, wherein M includes at least one of Ti, Zr, and Si, and 1≤n≤10.
2. The diaphragm according to claim 1, characterized in that Said 1≤n≤5.
3. The diaphragm according to claim 1 or 2, characterized in that: The Na2M n O 2n+1 Including Na2TiO3, Na2Ti2O5, Na2Ti5O 11 、Na2Ti6O 13 , Na2ZrO3, Na2SiO3, Na2Si2O5, Na2Si3O7, Na2Si5O 11 、Na2Si 10 O 21 At least one of .
4. The diaphragm according to any one of claims 1 to 3, characterized in that The Dv50 value of the sodium supplement compound ranges from 100 nm to 3 μm, preferably, from 100 nm to 1 μm.
5. The diaphragm according to any one of claims 1 to 4, characterized in that The diaphragm comprises a sodium-supplementing diaphragm, the sodium-supplementing diaphragm comprises the sodium-supplementing compound, and the thickness of the sodium-supplementing diaphragm ranges from 5 μm to 15 μm; preferably, from 7 μm to 13 μm; Alternatively, the diaphragm includes a base film and a sodium-supplementing layer disposed on the base film, the sodium-supplementing layer includes the sodium-supplementing compound, and the thickness of the sodium-supplementing layer ranges from 5 μm to 15 μm; preferably, from 7 μm to 13 μm.
6. The diaphragm according to any one of claims 1 to 5, characterized in that The membrane comprises a sodium-supplementing membrane, and the sodium-supplementing membrane further comprises a polymer, wherein the polymer is coated on the surface of the sodium-supplementing compound.
7. The diaphragm according to claim 5 or 6, characterized in that The sodium supplementing diaphragm also includes a toughening agent; Alternatively, the sodium-supplementing membrane further comprises a toughening agent, and the mass percentage of the toughening agent to the mass percentage of the sodium-supplementing membrane is 5% to 15%, preferably, 5% to 10%.
8. The diaphragm according to any one of claims 5 to 7, characterized in that The sodium supplementation membrane further comprises a polymer, wherein the polymer comprises at least one of polyethylene, polypropylene, polyethylene terephthalate, polyamide, and polyimide; And / or, the sodium supplementation membrane further comprises a toughening agent, and the toughening agent comprises at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, polyethylene oxide, sodium carboxymethyl cellulose, styrene butadiene rubber, hydroxypropyl methylcellulose, carboxy styrene butadiene latex or polyvinyl alcohol.
9. The diaphragm according to any one of claims 5 to 8, characterized in that The diaphragm further comprises a non-sodium-supplementing diaphragm, and the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm.
10. The diaphragm according to claim 9, characterized in that The diaphragm is used to be arranged on one side of the positive electrode plate or the negative electrode plate, and the sodium-supplementing diaphragm is arranged on the side of the non-sodium-supplementing diaphragm facing the positive electrode plate.
11. The diaphragm according to any one of claims 1 to 10, characterized in that The total thickness of the separator is in the range of 13 μm to 30 μm; preferably, 15 μm to 20 μm.
12. The diaphragm according to any one of claims 1 to 11, characterized in that The mass percentage of the sodium supplement compound to the total mass of the diaphragm is 5% to 30%, preferably 10% to 20%.
13. The diaphragm according to any one of claims 1 to 12, characterized in that The porosity of the separator is in the range of 30% to 45%, preferably, 35% to 45%.
14. The diaphragm according to any one of claims 1 to 13, characterized in that The diaphragm includes a sodium-supplementing diaphragm and a non-sodium-supplementing diaphragm, wherein the sodium-supplementing diaphragm is arranged on at least one side of the non-sodium-supplementing diaphragm, and the porosity of the sodium-supplementing diaphragm is less than or equal to the porosity of the non-sodium-supplementing diaphragm; preferably, the difference between the porosity of the non-sodium-supplementing diaphragm and the porosity of the sodium-supplementing diaphragm is less than or equal to 5%.
15. The diaphragm according to claim 14, characterized in that The porosity of the sodium supplementing membrane ranges from 30% to 45%, preferably, from 35% to 45%; And / or, the porosity of the non-sodium supplementing membrane ranges from 30% to 45%, preferably, from 37% to 45%.
16. A method for preparing a diaphragm according to any one of claims 1 to 15, characterized in that: include: Prepare the raw materials of the diaphragm, the raw materials of the diaphragm include sodium supplement compounds, the chemical formula of the sodium supplement compounds is NaAlO2, Na2M n O 2n+1 At least one of, wherein M comprises at least one of Ti, Zr, and Si, 1≤n≤10; The raw material of the diaphragm is prepared into a diaphragm.
17. The method for preparing a diaphragm according to claim 16, characterized in that: The process of preparing the raw material of the diaphragm into a diaphragm includes: The raw material of the diaphragm is added into the extruder of the diaphragm extrusion device, melt-extruded, and passed through a cooling roller to obtain a composite film substrate; The composite membrane substrate is subjected to a cold drawing process to form holes, subjected to a heat treatment and a hot drawing process to form holes, and shaped to obtain a sodium supplementing diaphragm.
18. The method for preparing a diaphragm according to claim 16 or 17, characterized in that: The step of preparing the raw material of the diaphragm also includes: The sodium supplement compound, the polymer and the toughening agent are stirred and mixed at a stirring speed of 400 r / min to 800 r / min and a stirring time of 0.5 h to 1 h to obtain a raw material for a diaphragm.
19. The method for preparing a diaphragm according to claim 18, characterized in that: The temperature of the cooling roller is 15°C to 30°C; and / or, the thickness of the composite film substrate is 10 μm to 25 μm; And / or, the cold drawing process is performed at a temperature of 15° C. to 30° C. and a stretching speed of 0.01 m / min to 0.1 m / min for uniaxial stretching; And / or, the heat treatment condition is heating at 15°C to 30°C below the melting point of the polymer for 30min to 60min; And / or, the conditions of the hot drawing process are uniaxial stretching at a temperature of 100° C. to 160° C., a stretching ratio of 1 to 5 times, and a stretching speed of 0.05 m / min to 0.5 m / min; And / or, the shaping treatment conditions are: temperature 15°C to 30°C, time 0.5h to 2h.
20. A process for preparing a battery, characterized in that: The preparation process of the battery comprises assembling a separator, a positive electrode sheet, and a negative electrode sheet, wherein the separator comprises the separator according to any one of claims 1 to 15; Alternatively, the preparation process of the battery includes assembling a diaphragm, a positive electrode sheet, and a negative electrode sheet, and the diaphragm includes a diaphragm prepared by the preparation method of the diaphragm according to any one of claims 16 to 19.
21. The process for preparing a battery according to claim 20, characterized in that: In the process of assembling the separator, positive electrode sheet and negative electrode sheet, it includes: The battery in which the separator is packaged with the positive electrode sheet and the negative electrode sheet is injected with liquid, and the battery is subjected to a formation treatment.
22. The process for preparing a battery according to claim 21, characterized in that: In the step of performing a formation treatment on the battery, the voltage range of the formation is 3V to 4.2V; And / or, the formation temperature is 45°C to 80°C; And / or, the formation time is 2h to 5h; And / or, the vacuum degree of the formed battery ranges from 0.01 MPa to 0.1 MPa.
23. The process for preparing a battery according to claim 21 or 22, characterized in that: After the step of performing formation treatment on the battery, the method further includes charging the battery, wherein the charging voltage ranges from 3V to 4.2V.
24. A battery, characterized in that: The battery comprises a battery prepared by the battery preparation process according to any one of claims 20 to 23.
25. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 24.
Citation Information
Patent Citations
Sodium ion battery electrode sheet, preparation method therefor, and sodium ion battery having electrode sheet
CN109565037A
Fluidization reaction method for synthesizing epoxypropane through gas-phase epoxidation of propylene and hydrogen peroxide
CN110256376A
Cooling mode of liquid cooling cable for liquid cooling charging socket of new energy electric vehicle
CN111200200A
Functionalized lithium supplementing diaphragm and preparation method thereof
CN111816822A
Lithium ion battery
CN112510247A